(3TQM GdNdGUI aj GdMSGHs - (3YHO GdQMje Hf CHi HcQ Hf SdjeGf GdeQYTis; (3HgGA GdOjf eMeO Hf MSjf GdMGQKj GdgeOGfj GdTjYj GdYGedj,J (B1031 (3g` s ((3eMeO Hf GdMGLi MSf GdNQHhJi s)
(3ChdgG (B:s
(3deG cGf Yde GdMSGH ef CLd GdYdhe dGeMGdI hXghQ YXe bOQg s
(3BNQgG (B:s
(3Ch ddHGbi LPQ gPG GbhGd dGjecf Cf jhLO eLPhQ HJdc GdUaI HQgGf ai GdKGfjI s
(3GdNdGUI ai GdMSGH GfXQ cTa GdXfhf L (B1 (3U` (B720s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdQjGVjGJs